Gender Gaps and the Rise of the Service Economy - Liwa Rachel Ngai; Barbara Petrongolo (Institute for the Study of Labor (IZA), 2014)
This paper investigates the role of the rise of services in the narrowing of gender gaps in hours and wages in recent decades. We document the between-industry component of the rise in female work for the U.S., and propose a model economy with goods, services and home production, in which women have a comparative advantage in producing market and home services. The rise of services, driven by structural transformation and marketization of home production, acts as a gender-biased demand shift raising women's relative wages and market hours. Quantitatively, the model accounts for an important share of the observed trends.
Keywords: E24; J22; J16; 330; gender gaps; structural transformation; marketization